Exploring the impact of sleep on emotional and physical well-being in professional cricketers: a cohort study over an in-season training period - Grewal, S.; Theijse, R. T.; Dunlop, G.; van Deurzen, D. F. P.; van den Bekerom, M. P. J.; Klautz, R. J. M.; Lefebvre, R. P.; Munsami, D.; Grewal, N. (Frontiers in Sports and Active Living, 2024)
Background Professional athletes navigate a multitude of unique challenges associated to sport-specific factors (e.g., training, travel and competition) and non-sport factors (e.g., performance pressure, stress and anxiety) that can interfere with healthy sleep behaviors. Sleep plays a key role in proper biopsychosocial development as well as short- and long-term biological, physical, psychological, and cognitive health. As poor sleep quality is known to impair proper brain function, this study aimed to investigate the effect of sleep quality on a professional athlete's ability to train, recover, and perform, as well as their overall emotional and physical well-being. Methods A cohort study was performed in 40 professional male cricket athletes from the Dutch national cricket team (mean age 26.5 ± 5.1 years). The athletes were monitored across a 22 weeks in-season training period. Sleep quality and overall emotional and physical well-being were assessed using daily sleep diaries and questionnaires which scored the readiness to train, stress levels, fatigue, muscle soreness and flu symptoms respectively. Quality of sleep and subsequent association with the consecutive elements of the well-being questionnaire were assessed through statistical using the student t-test and clinical differences with the methodology of Osoba and colleagues: <5% “no change”, 5%–10% “little change”; 10%–20% “moderate change”; and >20% “very much change”. Results The results demonstrated that the professional athletes assessed their sleep quality as average with a mean score of 3.4 out of 5. Lower perceived quality of sleep (<75th percentile) was correlated with a decreased readiness to train (mean score 3.2 [IQR: 3.0–4.0] vs. 3.5 [IQR: 3.0–5.0]; P < 0.001) and increased extent of muscle soreness (2.7 [IQR: 2.0–3.0] vs. 2.3 [IQR: 2–3]; P < 0.001), stress level (mean score 2.3 [IQR: 2.0–3.0] vs. 1.9 [IQR: 1.0–2.0]; P < 0.001) and perceived fatigue (mean score 2.9 [IQR: 2.0–3.0] vs. 2.3 [IQR: 2.0–3.0]; P < 0.001). Likewise, in patients with lower perceived quality of sleep, the proportion of players presenting with flu symptoms increased over 4-fold (4.1% vs. 17%; P < 0.001). Conclusions This study highlights that good sleep quality positively influences the overall emotional and physical well-being of professional athletes. Our results emphasize the importance of targeted sleep interventions to improve sleep quality and subsequently optimize psychological and physiological wellness.